Oxygen isotope heterogeneity of arc magma recorded in plagioclase from the 2010 Merapi eruption (Central Java, Indonesia). (1st October 2016) - Borisova, Anastassia Y.; Gurenko, Andrey A.; Martel, Caroline; Kouzmanov, Kalin; Cathala, Annick; Bohrson, Wendy A.; Pratomo, Indyo; Sumarti, Sri
Abstract: Chemical and isotopic compositions of magmatic crystals provide important information to distinguish between deep juvenile and crustal contributions. In this work, high-resolution multicollector secondary ion mass spectrometry data reveal strong variations of δ 18 O values in three plagioclase crystals (800–1700 μm) from two representative basaltic andesite samples of the 2010 Merapi eruption (Central Java, Indonesia). The δ 18 O values (from 4.6‰ to 7.9‰) are interpreted to reflect oxygen isotope heterogeneity in the melt composition during plagioclase growth. The lowest δ 18 O values (4.6–6.6‰) are found in anorthite-rich cores (An82–97 ), whereas higher δ 18 O values (5.7–7.9‰) are found in anorthite-poorer zones (An33–86 ), typically in crystal rims. Combining these new plagioclase δ 18 O data with δ 18 O of calc-silicate crustal xenoliths erupted between 1994 and 1998, the composition of glass inclusions hosted by the anorthite-rich plagioclase (An82 – 92 ), available experimental data, and the results of thermodynamic modeling using the Magma Chamber Simulator code, we conclude that the abundant anorthite-rich cores crystallized from a mantle-derived hydrous basaltic to basaltic trachyandesite melt that recharged a deeper (200–600 MPa) magma storage zone, whereas lower anorthite zones crystallized at shallower levels (100–200 MPa). The oxygen isotope variations in the plagioclase are explained by a two-stage model of interaction of the hydrous, mafic mantle-derived magma (1) with old crustal rocks depleted in 18 O due to high temperature alteration that yielded the low δ 18 O values in the anorthite-rich cores at deep levels (13–20 km), and later (2) with 18 O-enriched carbonate material that yielded the high δ 18 O values in anorthite-poorer zones at shallow levels (∼4.5–9 km). Thermodynamic modeling is consistent with ∼18 wt.% assimilation of crustal calc-silicate material at 925–950 °C and 100–200 MPa by the 2010 Merapi basaltic andesite magma prior to eruption. Timescales for plagioclase phenocryst growth and residence in the magmatic plumbing system are ⩽34 years. The combined data thus reveal efficient magma recharge and crustal assimilation processes that characterize the open-system magma storage and transport systems associated with the 2010 Merapi eruption.